PENGARUH SUPLEMENTASI MONENSIN DALAM TDN RANSUM YANG DITURUNKAN TERHADAP METABOLIT DARAH SAPI FH LAKTASI - Purwadi, Purwadi; Widiyanto, Widiyanto (Universitas Boyolali, 2022)
The aims of the present study was to determine the effect of monensin supplementation in ration TDN step-down on blood metabolit of lactation Friesian Holstein. The experiment made 4 treatments (T0: 73% TDN rations without monensin; T1: 73% TDN rations with 50 mg/cow/d monensin; T2: 68% TDN rations with 200 mg/cow/d monensin; T3: 68% TDN rations with 200 mg/cow/d monensin with 4 replications in group of 3,4,5 and 6 mounth of lactation. The variabel were a) dry matter intake, b) crude protein consumtion, c) TDN consumtion, e) blood glucose, f) blood urea, and g) blood insulin. The results showed that Monensin Supplementation In Ration TDN Step-Down has same mater of ration consumption and blood metabolit (P>0,05). The value of ration consumtion is 11,37; 10,89; 10,94 and 11,65 kg/d of dry mater intake; 1,58; 1,51; 1,51 and 1,59 kg/d of crude protein; and 8,27; 7,9; 7,44 and 7,94 kg/d of TDN. The value of blood metabolit is 67,9; 71,625; 65,05; and 67,70 mg/dl of blood glucose; 13,05; 19,925; 17,45; and 18,55mg/dl of blood urea; and 2,73; 2,79; 2,93 and 2,02 of blood insulin, respectively for T0, T1, T2 and T3. In conclusion of this experiment that monensin supplementation on TDN ration step-down not chance the ration consumtion and blood metabolit, that’s means monensin tended to increase the energy efficiency.